Keefektifan Layanan Bimbingan Kelompok Melalui Teknik Role Playing untuk Mengurangi Perilaku Bulliying - Stariah; Ahmad Syarqawi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The existence of bullying behavior in schools is certainly a scourge for educational units. With this research, namely applying the role playing method to class VII students at TanjungBalai 4 Public Middle School for the 2023-2024 academic year, this problem can be resolved. The research method used is a quasi-experimental research with a pretest and posttest control group design. The total population in this study was 51 students, and the research sample used a purposive sampling technique. In the t-test of the control group t count (4.869) > t table (2.064) it can be concluded that there is a significant decrease in the pre and post values of the control group. Whereas in the experimental group t count (6.466) > t table (2.064) it can be concluded that there is a significant decrease in the pre and post values of the experimental group.